Main Street with pedestrians and wagons, Nome, Alaska, June 23, 1900 - University of Washington Libraries. Special Collections Division
Handwritten on verso: Main St. Nome City. June 23, 1900. PH Coll 492.4 Nome, Alaska is one of the state's oldest cities and was incorporated on April 9, 1901. The city experienced a population boom in 1898 and 1899 when gold was discovered on nearby Anvil Creek. In 1934 Nome suffered a disastrous fire and during World War II it was an important stop for planes traveling to Russia for the Lend/Lease program. Today it is known for being the finish spot for the Iditarod sled-dog race.